Are older adults with excessive sodium intake at increased risk of hypohydration?. Issue 5 (29th January 2021) - Gamba, Marta; Moreira, Pedro; Borges, Nuno; Santos, Alejandro; Afonso, Cláudia; Amaral, Teresa F.; Padrão, Patrícia
Abstract: Background: Sodium intake is expected to affect water needs, although compensation mechanisms may not work efficiently particularly in older adults. The aim of this cross‐sectional study was to quantify the association between sodium excretion and hydration status in a representative sample of Portuguese older adults. Methods: A cluster sampling approach was used, representing Portuguese older adults (≥65 years) according to sex, education level and region. From a sample size of 1500 participants, 1318 were eligible for the present analysis. A 24‐h urine sample was collected, and volume, osmolality, creatinine and sodium were quantified. Free water reserve (FWR) was used to assess hydration status. Excessive sodium intake was defined as above 2000 mg day –1 as recommended by the World Health Organization. A multivariable binary logistic regression model was used to estimate the association between FWR and sodium excretion. Odds ratios (OR) and respective 95% confidence intervals (95% CI) were calculated. Results: Excessive sodium excretion was observed in 80.0% of women and 91.5% of men, whereas hypohydration affected 10.9% of women and 23.6% of men. After adjusting for confounders, excessive sodium excretion was associated with an increased risk of hypohydration among men (OR = 2.75; 95% CI = 1.06–7.15). Conclusions: These results stress the positive association between excessive sodium intake and hypohydration in men and highlight the need for implementing strategies regarding the reduction of salt consumption and the promotion of water intake. Abstract : The present study, based on a cross‐sectional study, provides evidence of the association between hydration status and sodium intake in a representative sample of 1500 Portuguese older adults, using 24‐h urine excretion to estimate both hydration status and sodium intake. Excessive sodium intake was associated with an increased risk of hypohydration among men, which was almost three‐fold higher than in those with an adequate sodium intake.